Effects of Delayed Carbohydrate Digestion on Energy Intake, Adiposity and Weight Gain in Congenic Lean and Obese-Diabetic Rats - Tulp, Orien L; Anderson, Michael E; Sainvil, Frantz (European Journal of Applied Sciences, 2024)
The burgeoning prevalence of obesity and overweight conditions including NIDDM and dysregulation of energy balance are rapidly approaching epidemic proportions in much of Western society and imposing a significant burden on available health care resources. Once diagnosed, treatment is typically a life-long effort to attenuate the continued progression of pathophysiologic sequela of the disorders. Since the predominate proportion of macronutrient energy source in most Western diets is often carbohydrate, typically more than 50% by weight at 4 kcals/gram, efforts to modulate the impact of dietary CHO on parameters of adiposity and weight gain were investigated. This study determined the effects of delayed carbohydrate digestion on energy intake and consequent weight gain groups of young adult, obese-NIDDM rats that were fed a USDA-formulated, hyperinsulinemic diet consisting of 54% sucrose plus essential fats, proteins, micronutrients and fiber for up to 8 weeks, or the same diet containing 150 mg/kg of (1,5 dideoxy-1,5-[(2-hydroxyethyl) imino]-D glucitol; generic miglitol). Measures of daily energy intake and weight gain were determined at weekly intervals. Adiposity was determined by dissecting major fat depots at the end of the study and determining adipose tissue mass and cellularity. Miglitol resulted in 20% less energy intake and weight gain, and corresponding decreases in adiposity after 8 weeks of study. The results of this study indicate that delayed carbohydrate digestion via the α-glucosidase inhibitor miglitol or other similar agents may be a useful adjunct in the regulation of food intake and in attenuating weight gain in man and animals in addition to their well-established effects as an adjunct in the treatment of impaired glycemic responses in obesity and NIDDM.